TEMPERATURE MONITORING USING HC-05 MODULE BASED ON ANDROID - Sumardi Sadi; Sri Mulyati (Jurnal Teknik, 2019)
Microcontrollers are now growing rapidly and are increasingly in demand in control system applications. Even now there are many microcontrollers in the form of modules. One module the most widely used microcontroller is Arduino. Arduino is a type of board that contains microcontroller. Combined with a Bluetooth module, this microcontroller can be connected via a Smartphone device. Arduino microcontroller board devices make it possible to process temperature reading data from the temperature sensor to be displayed to the display unit using Android based smartphone. Data processing results from this Arduino board will be transmitted using wireless Bluetooth media that is connected to an Android smartphone and will displayed on the LCD screen. This tool was created in order to facilitate the monitoring of temperature within a place, other tools according to field conditions. This tool uses an experimental method with steps it works Arduino as the parent that has been programmed and then gives input to the temperature sensor (LM35) for knowing the temperature of the room at that time. Before sending data, Bluetooth initialization needs to be done between Smartphone and HC 05. After that, the sensor sends data to the Arduino that will be forwarded into the LCD screen display and Smartphone device. The result of this tool is monitoring temperature against the room can be done effectively and efficiently and can be done as needed.